Novel exostosin‐2 missense variants in a family with autosomal recessive exostosin‐2‐related syndrome: further evidences on the phenotype. Issue 1 (24th October 2018) - Gentile, Mattia; Agolini, Emanuele; Cocciadiferro, Dario; Ficarella, Romina; Ponzi, Emanuela; Bellacchio, Emanuele; Antonucci, Maria F.; Novelli, Antonio
Abstract : Biallelic exostosin‐2 ( EXT2 ) pathogenic variants have been described as the cause of the Seizures‐Scoliosis‐Macrocephaly syndrome (OMIM 616682) characterized by intellectual disability, facial dysmorphisms and seizures. More recently, it has been proposed to rename this disorder with the acronym AREXT2 (autosomal recessive EXT2‐related syndrome). Here, we report the third family affected by AREXT2 syndrome, harboring compound missense variants in EXT2, p.Asp227Asn, and p.Tyr608Cys. In addition, our patients developed multiple exostoses, which were not observed in the previously described families. AREXT2 syndrome can be considered as a multiorgan Congenital Disorder of Glycosylation caused by a significant, but non‐lethal, decrease in EXT2 expression, thereby affecting the synthesis of the heparan sulfate proteoglycans, which is relevant in many physiological processes. Our finding expands the clinical and molecular spectrum of the AREXT2 syndrome and suggests a possible genotype/phenotype correlation in the development of the exostoses. Abstract : We describe two patients from an Italian family with autosomal recessive Exostin‐2‐related (AREXT2) syndrome, displaying two compound heterozygous missense variants in Exostin‐2 gene. The patients reported in this study extend the clinical and mutational spectrum of the AREXT2 syndrome, showing a possible geneotype/phenotype correlation in the development of the exostoses that can have an impact on clinical management of the patient. A clinical review of currently reported AREXT2 patients is provided.